1997
DOI: 10.1093/heapol/12.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Operational Factors Affecting Maternal Mortality in Tanzania

Abstract: Identification of the main operational factors in cases of maternal death within and outside the health care system is necessary for safe motherhood programmes. In this study, a follow-up was done of all 117 cases of maternal deaths in Ilala district, Dar es Salaam, 1991-1993, at all levels of care. In all, 79% received some medical care whereas 11% arrived too late for treatment. For each case the major operational factors and all health care interventions were defined through interviews with family members a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 0 publications
2
63
0
Order By: Relevance
“…Similarly, in Dar es Salaam, 72 of 93 maternal deaths in a referral hospital were related to sub-optimal medical care. 31 Phase 3 delay will influence delay in the two other phases. 32 It is even unethical to encourage women to seek treatment for problems related to pregnancy if obstetric services do not exist or do not function.…”
Section: Standard Of Carementioning
confidence: 99%
“…Similarly, in Dar es Salaam, 72 of 93 maternal deaths in a referral hospital were related to sub-optimal medical care. 31 Phase 3 delay will influence delay in the two other phases. 32 It is even unethical to encourage women to seek treatment for problems related to pregnancy if obstetric services do not exist or do not function.…”
Section: Standard Of Carementioning
confidence: 99%
“…Most studies that have examined the relationship of delays to maternal mortality have used subjective judgments of whether or not a delay occurred or simply specified the type of delay, rather than measuring specific time intervals between events. 9,10,25 The current study also had some limitations. A substantial number of cases in the database had missing data on the time of the start of hemorrhage, particularly for woman transferred into the referral hospital already bleeding; therefore, analyses of hemorrhage start times had a reduced number of cases.…”
Section: Discussionmentioning
confidence: 89%
“…The distance to be traveled is known to be an important variable in the seeking of health care generally [6,19], and for maternal care poor accessibility is significantly associated with death [4,10,[20][21][22][23][24][25]. Transportation delay has been found to be an important predictor of maternal mortality in highly populated areas [22].…”
Section: Discussionmentioning
confidence: 99%
“…Transportation delay has been found to be an important predictor of maternal mortality in highly populated areas [22]. A study reported that in Nepal only 32% of the population lived within 5 km of a health unit, and that distance was a strong factor in preventing access to care [23].…”
Section: Discussionmentioning
confidence: 99%